Synthesis and characterization of monolayer Er-doped MoS2 films by chemical vapor deposition. (15th July 2018) - Yang, Yong; Pu, Hongbin; Di, Junjie; Zang, Yuan; Zhang, Shan; Chen, Chunlan
Abstract: Herein, we firstly present Er-doped MoS2 films with a quasi-closed crucible method in chemical vapor deposition (CVD) system. ErCl3 ·6H2 O is exploited as the dopant and assistant agent. The Raman analysis indicates that doped samples are uniform and high crystalline quality which has two prominent peaks with the minimum FWHM ~4 cm −1 of E2g 1 . However, Er dopant caused a red-shift in PL spectra. Furthermore, doped samples present a clear absorption edge at 1.8 eV and a small split peak of B exciton, which is attributed to the formation of impurity levels in Er-doped MoS2 based on the DFT calculations. Graphical abstract: Unlabelled Image